PENGATURAN BATASAN UTANG DALAM PERMOHONAN PAILIT ANALISIS UNDANG-UNDANG PKPU DAN KEDUDUKAN PUTUSAN HAKIM - Silitonga, Yoas Panggawa; Gultom, Elisatris; Afriana, Anita (PALAR (Pakuan Law review), 2024)
ABSTRAKPenyelesaian utang piutang merupakan persoalan perdata yang dapat diselesaikan dengan berbagai mekanisme salah satunya mengajukan permohonan kepailitan. Pailit merupakan suatu keadaan berhenti membayar di mana Debitor dalam keadaan tidak mampu atau tidak mau untuk melakukan pembayaran terhadap utang-utang dari para kreditornya. Permohonan kepailitan akan diterima oleh pengadilan niaga jika memenuhi persyaratan Debitor memiliki utang kepada 2 (dua) atau lebih Kreditor dan terdapatnya satu utang yang telah jatuh waktu dan dapat ditagih, selanjutnya syarat ini harus dapat dibuktikan secara sederhana. Dalam praktik, ditemukan permohonan kepailitan yang telah memenuhi unsur, namun ditolak oleh pengadilan niaga dengan alasan jumlah minimal utang yang terlalu kecil. Tujuan yang hendak dicapai dalam penelitian ini adalah untuk menganalisis dan mengetahui kepastian hukum terkait batasan utang dalam UUKPKPU serta pertimbangan hakim yang menolak permohonan pailit dengan nilai jumlah utang yang kecil melalui tata cara penyelesaian gugatan sederhana atas dasar semua persyaratan telah terpenuhi ditinjau dari kepastian hukum.  Kata Kunci : Utang, Kepailitan, Putusan Hakim. ABSTRACTSettlement of debts is a civil matter that can be resolved through various mechanisms, one of which is filing a bankruptcy petition. Bankruptcy is a state of stopping payment where the Debtor is unable or unwilling to make payments on debts from his creditors. A bankruptcy petition will be accepted by the commercial court if it meets the requirements that the Debtor has debts to 2 (two) or more Creditors and there is one debt that has matured and can be collected, then this requirement must be proven simply. In practice, bankruptcy petitions have been found that have met the elements, but were rejected by the commercial court on the grounds that the minimum amount of debt is too small. The objectives to be achieved in this study are to analyze and determine the legal certainty related to debt limits in the UUKPKPU and the considerations of judges who reject bankruptcy petitions with small debt values through simple lawsuit settlement procedures on the basis that all requirements have been met in terms of legal certainty. The approach method used is normative juridical. The specifications of this study are descriptive analytical. This research stage includes the literature research stage, namely collecting secondary data consisting of primary, secondary and tertiary legal materials. Data collection techniques that are considered relevant and adequate to obtain secondary data in this study are document studies and interviews. Data analysis as data processing in the form of qualitative analysis, so that the results of the analysis are obtained in the form of legal certainty of rejection of bankruptcy applications on the basis of minimum debt limits reviewed from Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Keywords: Debt, Bankruptcy, Judge's decision